KEDUDUKAN WANITA DI IRAN: MENGUNGKAP PANDANGAN ULAMA SYâIAH - Sadik, M. (Hunafa: Jurnal Studia Islamika, 2005)
In Iran, woman emancipation does not undergo fundamental change compared with that in other Islamic worlds. In Iran, woman are still in subordinate position. It is within this context that conservative theological thought ofÂ  Shiâi ulamas (Islamic scholars), especially KhomeniÂ  gave a great contribution to the subordinating ofÂ  status of woman in Iran. This article tries to discussÂ  status of woman in Iran from ShiâiÂ  ulamaâs perspective.Â Kata Kunci: Kedudukan wanita, ulama Syiâah